(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
The study of the constitutive relationship of lunar soil is the key to a deep understanding of the mechanical properties of lunar soil and the subsequent construction of lunar bases. Previous models mostly focused on the strengthening behavior before the peak, while rarely reflected the post-peak softening and residual deformation stages during shear deformation. A new elastoplastic constitutive relation is derived with combining kinematic hardening model and initial shear stress, which effectively compensates for the shortcomings of existing constitutive models, and the validity of the model is verified by comparing with existed laboratory test results. The developed constitutive model not only effectively captures the shear dilatancy and softening characteristics of lunar soil simulant, but also requires fewer parameters to be easily determined by simple initial loading curves from direct shear tests, Furthermore, the influences of some key parameters on shear strength and softening behavior of lunar soil simulant can be easily obtained based on this constitutive model.